P054 2017 update of drug interactions detected using electronic care records (ECR). (8th June 2017) - Rafferty, PJ; McCarty, EM; Dinsmore, WW; Donnelly, CM; Emerson, CR; Hunter, M; Walker, E; Quah, SP
Abstract : Introduction: In 2014 the pharmacy team completed an interaction screen of all HIV patients on a boosted antiretroviral (ARV) regimen using then recently launched NIECR. We concluded that there was a need for primary and secondary care teams to screen and manage drug-drug interactions (DDI). 56 patients in 2014 required urgent clinical intervention. Methods: In 2014 we reported on patients taking a boosted ARV regimen for DDI; we continued this work for all patients and this year we reviewed our interaction screening database, to assess the following: Interaction screen documented, Number of patients issued medication by their GP, Percentage of interactions identified. Results: 1093 unique patient records, 887 (81.2%) have a recorded H&C number and interaction screen. 468/887 patients (53%) are prescribed medication by their GP with no or no significant interactions. 235/887 patients (27%) are prescribed medication by their GP where an interaction is identified by the MDT and managed. 122/887 patients (14%) do not obtain any medication from their GP. 9/887 patients (1%) have opted out of NIECR. No patients required an immediate clinical intervention. Discussion: The number of patients prescribed medications by their GP has increased from 45% in our 2014 report compared with 79.3% in this review. There was a significant improvement in the latest review of interactions and no patients were identified with serious interactions. A medicines reconciliation and interaction screen before initiating/switching treatment and prior to a clinic review has enabled our cohort to avoid clinically significant DDI.